Savagism and civilization : a study of the Indian and the American mind - Pearce, Roy Harvey (University of California Press, 1988)
First published in 1953, revised in 1964, and presented here with a new foreword by Arnold Krupat and new postscript by the author, Roy Harvey Pearce's Savagism and Civilization is a classic in the genre of history of ideas. Examining the political pamphlets, missionaries' reports, anthropologists' accounts, and the drama, poetry, and novels of the 18th and early 19th centuries, Professor Pearce traces the conflict between the idea of the noble savage and the will to Christianize the heathen and appropriate their land, which ended with the near extermination of Native American culure.